A rare case of symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) - Ardisa Pramudita; Inges Prawita Sari; Saraswati Anindhita Kusumaningrum; Sri Awalia Febriana; Fajar Waskito; Dyah Ayu Mira Oktarina; Niken Indrastuti (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) is a rare maculopapular drug eruption mediated by type IV hypersensitivity reaction and characterized by symmetrical erythematous involvement of flexural and intertriginous areas without systemic symptoms. This case report describes a rare presentation of SDRIFE and emphasizes the importance of early recognition and prompt withdrawal of the offending drugs. A 27-year-old woman presented with well-demarcated erythematous patches involving the axillae, inframammary region, antecubital fossae, inguinal, popliteal, and gluteal areas following exposure to multiple systemic medications, including cefadroxil, mefenamic acid, amoxicillin, oral dexamethasone, paracetamol, and loratadine. No mucosal involvement or systemic manifestations were observed. Histopathological examination revealed non-specific findings of cutaneous drug eruption. The clinical presentation met the established diagnostic criteria for SDRIFE, and drug causality assessment using the Naranjo Scale identified several medications as probable triggers. Management consisted of discontinuation of the suspected drugs, patient education to avoid re-exposure, and treatment with systemic and topical corticosteroids, resulting in marked clinical improvement within approximately two weeks. Differential diagnoses, including drug reaction with eosinophilia and systemic symptoms (DRESS), acute generalized exanthematous pustulosis (AGEP), and fixed drug eruption (FDE), were considered and excluded based on clinical features and laboratory findings. Histopathological findings in SDRIFE are known to be variable and non-specific. Although drug patch testing is recommended to identify the causative agent, it has not yet been performed in this case. In conclusion, this report highlights the diagnostic value of clinical criteria and the Naranjo Scale in SDRIFE. It also highlights the importance of early diagnosis and prompt drug withdrawal, particularly in patients exposed to multiple medications.